Karakteristik Fisiko-Kimia Tepung Ubi Jalar Ungu dengan Proses Perendaman Menggunakan Asam Sitrat - Imam Santosa; Acnes Meyta Puspa; Delvi Aristianingsih; Endah Sulistiawati (Universitas Ahmad Dahlan, 2019)
A study has been made in making purple sweet potato flour through the hydrolysis process using dilute citric acid. Sweet potatoes cut 3-5 mm, soaked in citric acid in various concentrations for a certain period, washed and drained. Sweet potatoes were then roasted at 70 degrees Celsius for 24 hours and then sieved with a mesh size of 200. The sieve results were analyzed for their physical, physicochemical content and compared with wheat flour. Soaking purple sweet potato using 0.01% citric acid produces purple sweet potato flour which is brightly colored, fine flour, decreasing the ash content with a very slight acid flour odor. The carbohydrate content of sweet potatoes is almost the same as wheat flour, and the fiber content of sweet potatoes is higher.